A comparative study of zinc protoporphyrin IX‐forming properties of animal by‐products as sources for improving the color of meat products. (30th November 2014) - Wakamatsu, Jun‐ichi; Murakami, Naoko; Nishimura, Takanori
Abstract The objective of this study was to obtain fundamental data for improving the color of meat products by using animal by‐products. We investigated zinc protoporphyrin IX (ZnPP)‐forming properties of various internal organs from pigs and chickens. ZnPP was formed in the liver, heart and kidney, whereas the porcine spleen and bile, which are involved in the metabolism of heme, did not have ZnPP‐forming properties. The optimum pH values were different among the internal organs and the ZnPP‐forming properties of porcine organs were better than those of chicken organs. The porcine liver showed the greatest ZnPP‐forming properties among all of the internal organs investigated in this study. The optimum pH value for ZnPP formation in the liver was lower than that of skeletal muscle. Oxygen did not inhibit the formation of ZnPP in the liver, unlike in skeletal muscle. Animal by‐products such as the liver have good ability for the formation of ZnPP and might be useful for improving the color of meat products.